Stool and Ruminal Microbiome Components Associated With Methane Emission and Feed Efficiency in Nelore Beef Cattle - Andrade, Bruno G. N.; Bressani, Flavia A.; Cuadrat, Rafael R. C.; Cardoso, Tainã F.; Malheiros, Jessica M.; de Oliveira, Priscila S. N.; Petrini, Juliana; Mourão, Gerson B.; Coutinho, Luiz L.; Reecy, James M.; Koltes, James E.; Neto, Adhemar Z.; et al. (Frontiers in Genetics, 2022)
Background: The impact of extreme changes in weather patterns in the economy and human welfare are some of the biggest challenges our civilization faces. From anthropogenic contributions to climate change, reducing the impact of farming activities is a priority, since it is responsible for up to 18% of global greenhouse gas emissions. To this end, we tested whether ruminal and stool microbiome components could be used as biomarkers for methane emission and feed efficiency in bovine, by studying 52 Brazilian Nelore bulls belonging to two feed intervention treatment groups, i.e., conventional and byproducts-based diets. Results: We identified a total of 5,693 Amplicon Sequence Variants (ASVs) in the Nelore bulls' microbiomes. Differential abundance (DA) analysis with the ANCOM approach identified 30 bacterial and 15 archaea ASVs as DA among treatment groups. Association analysis using Maaslin2 software and a linear mixed model indicated that bacterial ASVs are linked to the host's residual methane emission (RCH4) and Residual Feed Intake (RFI) phenotypes variation, suggesting their potential as targets for interventions or biomarkers. Conclusion: The feed composition induced significant differences in both abundance and richness of ruminal and stool microbial populations in ruminants of the Nelore breed. The industrial byproducts based dietary treatment applied to our experimental groups influenced the microbiome diversity of bacteria and archaea, but not of protozoa. ASVs were associated with RCH4 emission and RFI in ruminal and stool microbiomes. While ruminal ASVs were expected to influence CH4 emission and RFI, the relationship of stool taxa, such as Alistipes and Rikenellaceae (gut group RC9), with these traits was not reported before and might be associated with host health due to their link to anti-inflammatory compounds. Overall, the ASVs associated here have the potential to be used as biomarkers for these complex phenotypes.